Germination behaviour of chlamydospores of some mutants of Gliocladium virens - and D.K. AGARWAL, M.K. BAG*, S. PAN (Indian Phytopathology, 2002)
The genninability of chlamydospores of a few selected mutant isolates, viz., 100 KR Ml, 100 KR M2 and 50 KR M3 of Gliocladium virens developed by gamma-radiation was studied alongwith their wild counterpart (15 GVl) under different artificial and natural habitats. Acidic pH favours germination of chlamydospores of both mutants as well as wild isolates. However, pH 3.5 and below reduced germination significantly. Similarly, carbon in glucose and nitrogen in ammonium-nitrate form gave augmented germination over control. The chlamydospores showed reduced germination both in unsterilized soil leachets and on sterilized soil surface. Annuling the stasis effect of either soil leachet or of soil with steam favour germination of chlamydospores.